Produção, caracterização e aplicação de anticorpos monoclonais contra o vírus da Bronquite Infecciosa das Galinhas - Conrad, Neida Lucia (2013)
The infectious bronchitis (IB) is an acute and highly contagious disease caused by a coronavirus that infects mainly cells of the respiratory and genitourinary of chicken. The economic importance of this disease results from decreased production, such as internal and external quality of eggs, reduced hatchability, feed efficiency and weight gain, increased mortality, condemnation of carcasses at slaughter, and also with drugs spending to suppress secondary bacterial infections. The diagnosis of IB is based on virus isolation, together with serology. The use of monoclonal antibodies (MAbs) has been collaborated to diagnosis of this type of disease, but their use are still limited because the MAbs used are imported, increasing the cost of such methodologies. This work reports the production, characterization and application of MAbs against the virus of infectious bronchitis (IBV). For the production of MAbs, Balb/c mice were immunized intraperitoneally with classic IBV (M41) or variant IBV. We generated two hybridomas secreting MAbs anti-IBV (IgM isotype) from the fusion of B-lymphocytes from a mouse immunized with the variant IBV and myeloma cells. Following the characterization by ELISA and Western blot, it was observed that MAbs recognize the IBV classic and variant, showing more intense reactions with IBV variant. The AcM 2 G4 seems to be specific for protein S1. The applicability of the MAbs was assessed using the immunohistochemistry technique on histological tissues of birds inoculated experimentally with classic IBV. These MAbs anti-IBV had the same pattern of label of the MAb used as positive control, labeling predominantly inflammatory cells. This result can be explained by the fact that in severe cases of infection with IBV, the antigen may be located also in inflammatory cells. It was concluded that the MAbs obtained have potential for use in immunodiagnostic for IB.